2020
DOI: 10.1016/j.ehb.2020.100858
|View full text |Cite
|
Sign up to set email alerts
|

Younger, dissatisfied, and unhealthy – Relative age in adolescence

Abstract: We investigate whether relative age (i.e. the age gap between classmates) affects life satisfaction and health in adolescence. We analyse data on students between 10 and 17 years of age from the international survey 'Health Behaviour in School-Aged Children' and find robust evidence that a twelve-month increase in relative age (i.e. the hypothetical maximum age gap between classmates) i) increases life satisfaction by 0.168 standard deviations, ii) increases selfrated general health by 0.108 standard deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…As a robustness check, teacher-reported SDQ was analysed but largely yielded the same results (see Chapters 4 and 5). Life satisfaction is a cognitive evaluation of subjective wellbeing (Fumarco et al, 2020) that is strongly related to depression (Headey et al, 1993). The Piers-Harris scale is designed to measure a child's self-concept, with a higher score indicating a more positive self-concept.…”
mentioning
confidence: 99%
“…As a robustness check, teacher-reported SDQ was analysed but largely yielded the same results (see Chapters 4 and 5). Life satisfaction is a cognitive evaluation of subjective wellbeing (Fumarco et al, 2020) that is strongly related to depression (Headey et al, 1993). The Piers-Harris scale is designed to measure a child's self-concept, with a higher score indicating a more positive self-concept.…”
mentioning
confidence: 99%
“…Of the remaining four studies, Duncan et al (2022) found no association between relative age and adolescents' mental health while Fenzel (1992) found that mental health was lower among children who were relatively young. Two further studies reported increased self‐reported psychosis (DeVylder et al, 2015) among relatively younger adults and decreased life satisfaction in relatively younger children (Fumarco et al, 2020). Overall, these nine studies suggest that those who are relatively young are at greater risk of negative outcomes, but effect sizes tend to be very small, and findings are not always consistent.…”
Section: Resultsmentioning
confidence: 99%
“…Challenges experienced by relatively younger children (e.g., less school experience, teacher‐reported language and behaviour difficulties, see Carroll, 1992; Cobley et al, 2009; Norbury et al, 2016) combined with their poorer academic performance may contribute to them being disproportionately diagnosed with special educational needs (Cobley et al, 2009; Wilson, 2000), developmental disorders (Dhuey & Lipscomb, 2010; Elder & Lubotsky, 2009; Gledhill et al, 2002; Wallingford & Prout, 2000), temperamental differences such as increased levels of hyperactivity (Mühlenweg et al, 2012), and being over‐represented in referrals to specialist Child and Adolescent Mental Health Services (Berg & Berg, 2014). Risky health behaviours have also been associated with relatively young students (Bahrs & Schumann, 2020; Routon & Walker, 2022) along with lowered self‐reported general health and life satisfaction in adolescence (Fumarco et al, 2020). The link between being relatively young at school and mental health problems has also been supported by Thompson et al (1999) who identified a significant link between being relatively young and suicidal behaviour in Canadian youths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they are more immature regarding social, cognitive and motor development. Being compared with older and more mature peers may lead to problematization of relative immaturity and to overdiagnosis and medicalization, and negatively impact mental health and self-esteem [9][10][11] . Such influences on children of their chronological age relative to their classmates' age is often referred to as "relative age effect".…”
Section: Introductionmentioning
confidence: 99%